Ox Cart, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
Picturesque postcard featuring labourers using ox drawn carts to carry their load.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Draft animals--Trinidad and Tobago; Oxen--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Working class--Trinidad and Tobago; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Rural transportation--Trinidad and Tobago; Transportation--Trinidad and Tobago; [1960]